The accuracy of measures of institutional trust in household surveys Evidence from the oecd trust database - González, Santiago (OECD Statistics Working Papers, 2017)
A key policy concern in recent years has been the decline in levels of trust by citizen in public institutions. Trust is one of the foundations upon which the legitimacy and sustainability of political systems are built. It is crucial to the implementation of a wide range of policies and influences people's behavioural responses to such policies. However, despite its acknowledged importance, trust in public institutions is poorly understood and is not consistently measured across OECD countries. The OECD Trust Database brings together information from a wide range of different household surveys containing measures of trust and combines this with information on other social and economic outcomes. The size of the database and range of covariates make it possible to identify the underlying patterns captured by survey based measures of trust in institutions and systematically test the accuracy (i.e. reliability and validity) of these measures. Reliability is tested by examining the consistency of measures of institutional trust across different surveys and between different waves of the same survey. Validity is harder to test than reliability. It is however possible to examine the construct validity of institutional trust measures by looking at whether these measures show the expected correlation with other social and economic variables on a cross-country basis. Analysis of item-specific non-response rates provides important additional information on the face validity of institutional trust measures